The Role of OmpR in the Expression of Genes of the KdgR Regulon Involved in the Uptake and Depolymerization of Oligogalacturonides in Yersinia enterocolitica - Nieckarz, Marta; Raczkowska, Adrianna; Jaworska, Karolina; Stefańska, Ewa; Skorek, Karolina; Stosio, Dorota; Brzostek, Katarzyna (Frontiers in cellular and infection microbiology, 2017)
Oligogalacturonide (OGA)-specific porins of the KdgM family have previously been identified and characterized in enterobacterial plant pathogens. We found that deletion of the gene encoding response regulator OmpR causes the porin KdgM2 to become one of the most abundant proteins in the outer membrane of the human enteropathogen . Reporter gene fusion and real-time PCR analysis confirmed that the expression of is repressed by OmpR. We also found that expression is subject to negative regulation by KdgR, a specific repressor of genes involved in the uptake and metabolism of pectin derivatives in plant pathogens. The additive effect of and mutations suggested that KdgR and OmpR regulate expression independently. We confirmed that occurs in an operon with the gene, encoding the periplasmic pectate lyase PelP. A pectinolytic assay showed strong upregulation of PelP production/activity in a strain lacking OmpR and KdgR, which corroborates the repression exerted by these regulators on . In addition, our data showed that OmpR is responsible for up regulation of the gene encoding the second specific oligogalacturonide porin KdgM1. This indicates the involvement of OmpR in the reciprocal regulation of both KdgM1 and KdgM2. Moreover, we demonstrated the negative impact of OmpR on transcription, which might positively affect the expression of genes of the KdgR regulon. Binding of OmpR to the promoter regions of the operon, and and genes was confirmed using the electrophoretic mobility shift assay, suggesting that OmpR can directly regulate their transcription. We also found that the overexpression of porin KdgM2 increases outer membrane permeability. Thus, OmpR-mediated regulation of the KdgM porins may contribute to the fitness of in particular local environments.